Modelling the human immune response mechanisms to mycobacterium tuberculosis infection in the lungs - Gesham Magombedze; Winston Garira; Eddie Mwenje (Mathematical Biosciences and Engineering)
This work elaborates on the effects of cytotoxic lymphocytes (CTLs)and other immune mechanisms in determining whether a TB-infected individualwill develop active or latent TB. It answers one intriguing question: whydo individuals infected with Mycobacterium tuberculosis (Mtb) experience differentclinical outcomes? In addressing this question, we have developed amodel that captures the effects of CTLs and the combined effects of CD4+helper T cells (Th1 and Th2) immune response mechanisms to TB infection.The occurrence of active or latent infection is shown to depend on a number offactors that include effector function and levels of CTLs. We use the model topredict disease progression scenarios, including primary, latency or clearance.Model analysis shows that occurrence of active disease is much attributedto the Mtb pathogen ability to persist outside the intracellular environmentand that high levels of CTLs result in latent TB, while low levels of CTLsresult in active TB. This is attributed to the CTLs’ ability to directly killinfected macrophages and the bacteria inside the infected macrophages. Thestudy suggests directions for further basic studies and potential new treatmentstrategies.